Implementation of Total Quality Management in the Ministry of Religion-Based Education - Muhammad Hakim Azizi; Syamsul Bakri; Siti Choiriyah (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2023)
Total Quality Management (TQM) is a school management concept in carrying out the process of education, which can certainly provide a better chance for the development, demands, and dynamics of society. This study aims to find out as well as describe the factors that support the successful implementation of total quality management at SD IT Al-Anis Kartasura, Sukoharjo. Evidence of the successful implementation of TQM at SD IT AL-Anis is shown by the continued increase in input from SD IT Al-Anis Kartasura, often exceeding the specified quota; Including many outputs achieved in the form of achievements, both by teachers and students, as well as the birth of high-competitive outcomes. This research used a qualitative descriptive method, which results in the finding that the successful implementation of TQM is supported by the leadership style of a school principal, through a process from top to bottom in reverse, good communication between stakeholders of educational institutions, rewards, and punishments that are by needs, as well as the existence of a Measurement of the quality of education that continues to be carried out both internally and externally.